2019
DOI: 10.1021/acs.jpcb.9b06783
|View full text |Cite
|
Sign up to set email alerts
|

Interaction and Dynamics in a Fully Biodegradable Glucose-Containing Naturally Abundant Deep Eutectic Solvent: Temperature-Dependent Time-Resolved Fluorescence Measurements

Abstract: A new room-temperature deep eutectic solvent (DES) composed of glucose, urea, and water has been prepared and its relaxation dynamics explored via temperature-dependent time-resolved fluorescence measurements employing hydrophilic and hydrophobic solute probes. Differential scanning calorimetry measurements indicate a glass transition temperature (T g) of ∼236 K. Measured viscosity coefficients (η) vary from ∼600 to ∼100 cP in the temperature range 318 ≤ T/K ≤ 343 and exhibit Arrhenius-type temperature depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 111 publications
3
23
0
Order By: Relevance
“…32,33,35,36 This is not surprising as these TDFFS studies were based on the TCSPC technique, where a large portion of the early part of the total dynamics was missed due to limited time resolution (typically 25−50 ps). 32,33,35,36 It is important to note that the reported magnitude of the total shifts of C153 in the earlier studies of solvation dynamics in common ILs, 48 which captured the complete dynamics, are comparable to the present values. This indicates that we have been able to capture almost the entire solvation dynamics in the present case.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33,35,36 This is not surprising as these TDFFS studies were based on the TCSPC technique, where a large portion of the early part of the total dynamics was missed due to limited time resolution (typically 25−50 ps). 32,33,35,36 It is important to note that the reported magnitude of the total shifts of C153 in the earlier studies of solvation dynamics in common ILs, 48 which captured the complete dynamics, are comparable to the present values. This indicates that we have been able to capture almost the entire solvation dynamics in the present case.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Notwithstanding their applications, , the structure and dynamics of the DESs are not very well understood from the studies made so far on the diffusion dynamics of constituents of the DESs , and translational and rotational diffusion dynamics of organic probe molecules in these media. While Abbott and co-workers investigated molecular and ionic diffusion of the constituents in these solvents using pulsed field gradient NMR spectroscopy, ,, Biswas and co-workers studied rotational diffusion of several molecular systems in a number of DESs to understand the dynamics of these liquids. We have recently investigated the translational and rotational diffusion dynamics of some probe molecules employing fluorescence correlation spectroscopy and time-resolved fluorescence anisotropy measurements. These studies have revealed significant to moderate spatial and/or dynamic heterogeneity of these DESs, depending on the constituents.…”
Section: Introductionmentioning
confidence: 99%
“…These systems are also rich and diverse in basic scientific aspects because of the “metastability” arising from being in the liquid phase at temperatures lower than the melting temperatures of the individual components. The signature of metastability has probably been reflected via the pronounced fractional viscosity dependence of relaxation rates at temperatures ∼50–150 K above the respective thermodynamic glass transition temperatures for a variety of DESs. , This is striking because such a strong viscosity decoupling of relaxation rates is known to occur for deeply supercooled liquids near glass transition, where spatial inhomogeneity is believed to characterize the liquid structure at such low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…In many of these papers, the inhomogeneity of the microscopic structural features is underlined, that is also, as mentioned before, the reason for the liquid formation. Fluorescent probe studies were also used in these approaches in order to investigate the structural features of these systems [40][41][42][43][44][45]. In particular, a great deal of effort has recently been put in trying and understanding the difference between spatial and temporal heterogeneity in various DESs.…”
Section: Introductionmentioning
confidence: 99%